2020
DOI: 10.1017/s004740452000069x
|View full text |Cite
|
Sign up to set email alerts
|

Modulating action through minimization: Syntax in the service of offering and requesting

Abstract: This study uses data from a shoe-repair shop, supplemented by data from medical and mundane contexts, to analyze three progressively minimal grammatical formats used to implement offers and requests in interaction (i.e. do you want…?, you want…?, and want…?). We argue that this cline of minimality reflects a cline of the action-initiator's stance, from relatively weak to strong (respectively), regarding their expectation that the action will be accepted or complied with. In doing so, we illustrate that, as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…We find that participants orient to these subtle, emergent contingencies in the grammatical design of proposals for joint activity, formulating their actions to enact stances that are fitted to, and accounted for by, the contexts of their deployment. As a cline reflecting recipients' disposition toward acceptance has also been shown to affect the design of offers and imperatives (see Raymond, et al 2021;Zinken & Deppermann 2017), our findings further support the claim of speakers' consistent orientation to recipients' buy-in as a truly fundamental dimension of the grammar of recruitment-related actions. Continued exploration of the relevance of this cline across action types seems highly warranted.…”
Section: The Action Of Proposing a Joint Activitysupporting
confidence: 78%
See 1 more Smart Citation
“…We find that participants orient to these subtle, emergent contingencies in the grammatical design of proposals for joint activity, formulating their actions to enact stances that are fitted to, and accounted for by, the contexts of their deployment. As a cline reflecting recipients' disposition toward acceptance has also been shown to affect the design of offers and imperatives (see Raymond, et al 2021;Zinken & Deppermann 2017), our findings further support the claim of speakers' consistent orientation to recipients' buy-in as a truly fundamental dimension of the grammar of recruitment-related actions. Continued exploration of the relevance of this cline across action types seems highly warranted.…”
Section: The Action Of Proposing a Joint Activitysupporting
confidence: 78%
“…Researchers have drawn on such interactional features as contingency and entitlement (Curl 2006;Curl & Drew 2008;Fox & Heinemann 2016), expectation of being complied with (Raymond et al forthcoming), recipient's current activity trajectory (Zinken & Deppermann 2017), and deontic stance (Couper-Kuhlen & Thompson forthcoming) to account for variation in grammatical format choice in request, offer, and advice-giving sequences. In alignment with what Raymond et al (2021) have found in the case of offers, our study of proposals focuses on the estimation of proposers as to the likelihood of their proposal being embraced.…”
Section: Introductionmentioning
confidence: 90%
“…? formats for offers and requests, Raymond et al (2020) show that more minimal forms (without pronoun and/or auxiliary) display stronger expectation of a preferred response.…”
Section: Lean Syntax In Multimodal Interactionmentioning
confidence: 76%
“…Approximately 100 when-formulations were present in our initial systematic collection, with various additional cases being considered as well as our investigation proceded. Our reason for focusing on this particular grammatical format is that, as we will see, we find it used in the construction of both demonstrably recognitional and demonstrably non-recognitional references to time; standardizing on this referential format thus offers an opportunity to examine the nature of recognitionality in a somewhat controlled turn-design structure (on which, see Raymond et al, 2021b). Moreover, targeting this format would allow us to interrogate references to both the past and the future (each with its own particulars involving recognitionality), as well as explore a range of actions that such references can be implicated in or are otherwise "accomplice to" (Heritage, 1984a:299;Jefferson, 1984:216), a point to which we will return in the Discussion.…”
Section: Methodsmentioning
confidence: 99%